Frequency of Brucellosis and Hepatitis B Virus Seropositivity in Patients with Chronic Lymphocytic Leukemia - Ekinci, Omer; Ebinç, Senar; Doğan, Ali; Demir, Cengiz (My University, 2020)
Objective: Patients with chronic lymphocytic leukemia (CLL) show defective cellular and humoral immune responses. Although such immune failure is known to be associated with an increase in the frequency of particularly gram–positive and –negative bacterial infections, data on the increase in the frequency of zoonoses such as brucellosis and viral infections such as the hepatitis B virus (HBV) are inconclusive. This study aims to investigate the frequency of brucellosis and HBV seropositivity in patients diagnosed with CLL. Methods: Patients followed–up for CLL between 2005 and 2019 were evaluated. Results of patients who were tested for HBsAg and anti–HBs serology using the ELISA assay and for brucellosis using the serum agglutination (Wright) test were recorded. Demographic data and laboratory results of all patients included in the study were evaluated. Results: This study included 188 patients diagnosed with CLL, of whom 56 (29.8%) were female and 132 (70.2%) were male. Median age was 62 (33–92) years. Complete blood count parameters at diagnosis were as follows: median leukocyte count, 54.4×109/L (5.1–312.3×109/L); median lymphocyte count, 42.3×109/L (2.8–296.8×109/L); median platelet count, 148×109/L (86.3–342.3×109/L); median hemoglobin level, 13.4 g/dL (8.5-16.9 g/dL). HBsAg and anti–HBs were tested in 142 patients. A total of 16 (11.27%) patients were HBsAg–positive; with 5 (3.52%) positive cases in females and 11 (7.75%) in males. A total of 105 (73.95%) patients were anti–HBs–positive; with 32 (22.54%) positive cases in females and 73 (51.41%) in males. Wright agglutination test was performed on 82 patients. A total of 4 (4.88%) patients reacted positively to the Wright test; with 3 (3.66%) positive cases in females and 1 (1.22%) in males. Conclusion: Compared with the epidemiological studies conducted in the same region; the rate of positive reactions to the Wright agglutination test was consistent with the literature data; however, a higher rate of HBsAg positivity was determined. This may be linked to the increase in the risk of HBV transmission due to the immune defect caused by CLL or the immunosuppressive picture induced by the medication used in the treatment, or viral reactivation.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Patoloji; Mikrobiyoloji; Sağlık Bilimleri ve Hizmetleri